A case of cutaneous metastasis mimicking herpes zoster rash. (2018) - Chiang, Angela; Salomon, Nadim; Gaikwad, Rahul; Kirshner, Jonathan
Abstract: Cutaneous metastasis is a rare occurrence and often is confused with infectious etiology most commonly herpes zoster rash. We present a case 49 year old male with history of metastatic colon cancer with persistent dermatomal vesicular rash that thought to be due to herpes zoster. A skin biopsy eventually revealed malignant cells.